Kebahagiaan Hubungan Suami Isteri Ditinjau dari Ketrampilan Komunikasi Asertif - Muslimah Zahro Romas (LPPM Universitas Proklamasi 45, 2011)
Objective of this research is to explain the relationship between couple’s marriage happiness and assertive communication skill. This assertive communication skill actually will direct people to communicate honestly without aggressively.This kind of social interaction will be occurred when those couples have matured emotional level. Matured emotional level will make people enjoy to each other, devoid of insulting, and becoming comfortable. Seventy four people participated in this research. Relationship of those two variables revealed that couple's assertive communication skill influenced their marriage happiness (rxy = .457, p = .0000 or p<.001). This influence was about 20.9 percent.